Outcomes of mentoring programs in psychiatry training: a literature review. (June 2019) - You, Daniel; Kealy-Bateman, Warren
Objectives: This literature review aimed to outline the evidence regarding the outcomes of formal mentoring programs for training psychiatrists. Methods: An electronic search of Ovid MEDLINE, EMBASE, Ovid PsycINFO and The Cochrane Library was conducted. Results: A total of 17 articles fulfilled inclusion criteria. Positive outcomes of mentorship include promotion of research, perpetuation of further mentorship, increased perceived support and enhancement of teaching skills. One article reported a negative outcome. Conclusions: Current evidence regarding mentorship in psychiatry is limited and there is a lack of clarity regarding the relationship between positive outcomes and mentorship. Components of the included programs may act as confounders. Mentorship, protected teaching time, and didactic teaching may be important to encourage research. Other potential benefits of mentorship include enhanced career guidance, perceived support, and enriched teaching skills.